Randomized Placebo‐/Sham‐Controlled Trials of Spinal Cord Stimulation: A Systematic Review and Methodological Appraisal. Issue 1 (15th July 2019) - Duarte, Rui V.; McNicol, Ewan; Colloca, Luana; Taylor, Rod S.; North, Richard B.; Eldabe, Sam
Abstract : Objectives: The recent availability of paraesthesia/sensation free spinal cord stimulation (SCS) modalities allow the design of clinical trials of SCS using placebo/sham controls and blinding of patients, clinicians, and researchers. The aims of this study were to: 1) systematically review the current evidence base of randomized controlled trials (RCTs) of SCS placebo/sham trials and 2) to undertake a methodological critique of their methods. Based on this critique, we developed a checklist for the design and reporting of future RCTs of SCS. Materials and Methods: Electronic data bases were searched from inception until January 2019 for RCTs of SCS using a placebo/sham control. RCTs with only an active comparator arm were excluded. The results are presented as a narrative synthesis. Results: Searches identified 12 eligible RCTs. SCS modalities included paraesthesia stimulation, subthreshold, burst, and high‐frequency SCS and were mainly conducted in patients with failed back surgery syndrome, complex regional pain syndrome, and refractory angina. The quality and transparency of reporting of the methods of placebo stimulation, blinding of patients, clinicians, and researchers varied markedly across studies. Conclusions: To date the methods of placebo/sham control and blinding in RCTs have been poorly reported, leading to concerns about the validity and replicability of the findings. Important aspects that need to be clearly reported in the design of placebo‐/sham‐controlled RCTs of SCS include the transparent reporting of stimulation programming parameters, patient position during perception threshold measurement, management of the patient handheld programmer, frequency of recharging, and assessment of the fidelity of blinding.